2019
DOI: 10.1186/s13223-019-0329-2
|View full text |Cite
|
Sign up to set email alerts
|

Availability and affordability of medicines and diagnostic tests recommended for management of asthma and chronic obstructive pulmonary disease in sub-Saharan Africa: a systematic review

Abstract: Background Early accurate diagnosis and sustainable availability of affordable medicines and diagnostic tests is fundamental in optimal management of asthma and chronic obstructive pulmonary disease (COPD). We systematically reviewed original research articles about availability and affordability of medicines and diagnostic tests recommended for management of asthma and COPD in sub-Saharan Africa (SSA). Methods We searched PubMed, Scopus and African Journal Online for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Similar to previous studies [41][42][43][44], many countries reported limited availability of essential NCD medicines and technologies. Only Cabo Verde and Mauritius report availability of all ten essential NCD medicines and six essential NCD technologies in their PHC facilities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to previous studies [41][42][43][44], many countries reported limited availability of essential NCD medicines and technologies. Only Cabo Verde and Mauritius report availability of all ten essential NCD medicines and six essential NCD technologies in their PHC facilities.…”
Section: Discussionsupporting
confidence: 85%
“…Cabo Verde has achieved these targets through strong political commitment to strengthen PHC services as part of their UHC agenda [ 45 ]. The limited availability of affordable medicines and diagnostic tests is a complex challenge in sub-Saharan Africa [ 43 ]. Minimal competition among few numbers of suppliers in LMICs affects medicine supply and cost.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, drugs for CRDs can be less available and affordable, especially in low-income settings, including SSA, where the availability and affordability of medicines and diagnostics recommended for the management of asthma and COPD is a big challenge. 10 Fortunately, the rational use of pharmacotherapy for CRDs could be complemented by non-pharmacological treatments. For COPD, pulmonary rehabilitation (PR) is well established as a highly effective intervention that improves symptoms, quality of life and survival 11 , and a recent trial has shown a substantial reduction in the risk of readmission in patients who undertake PR immediately after admissions for COPD.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Our study in Sudan focussed only on district level health facilities including those where an integrated approach to delivering a package of care for CLD is operational (29). These facilities had peak ow meters and were more likely to have asthma guidelines, both of which were found to be frequently unavailable for CLD care in sub-Saharan African contexts (30). However, experience with asthma care and overall higher readiness for CLD care did not translate to improved care of CLD in general as seen in failure of the facilities to diagnose even a case of COPD from among over 12,000 adult patients seen over a month's period.…”
Section: Discussionmentioning
confidence: 99%